Effect of Job Rotation and Experience on Work Achievement of Youth Services and Sports Culture and Tourism of Labuhan Batu District - Raja Tua Ritonga; Elvina Elvina; Christine Herawati Limbong (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyzeThe Effect of Job Rotation and Experience on Work Performance of Employees of the Department of Youth and Sports, Culture and Tourism, Labuhan Batu Regency. This type of research is quantitative, the place of this research is the employee of the Department of Youth and Sports, Culture and Tourism, Labuhan Batu Regency, whose address is at Jalan WR. Supratman, No. 10, Rantau Utara, Labuhan Batu Regency, North Sumatra. Data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The population in this study were 70 employees of the Department of Youth and Sports, Culture and Tourism, Labuhan Batu Regency. Saturated sampling technique is a sampling technique when all members of the population are used as samples. Since the number of employees of the Regional Revenue Agency Office of Labuhan Batu Regency is 70 people (less than 100 people), all employees are taken as objects of research. The structural equation of multiple linear regression in this study is Y=1,324+0,440X1+0,364X2. The B value in job rotation (B1) is 0.440, the experience value (B2) is 0.364 and the constant value (a) is 1.324. The description of the multiple linear regression structural equation shows that the job rotation variables (X1), and experience (X2) have a positive direction coefficient on work performance. The value of Fcount is 36.577> Ftable 2.74 with a significance value of 0.000 <0.05. The results showed that job rotation (X1) and experience (X2) simultaneously had a positive and significant effect on work performance (Y).